2008
DOI: 10.1097/01.prs.0000304612.72899.02
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Collagen Induction Therapy: An Alternative Treatment for Scars, Wrinkles, and Skin Laxity

Abstract: Percutaneous collagen induction was started in 1997 and has proved to be a simple and fast method for safely treating wrinkles and scars. As opposed to ablative laser treatments, the epidermis remains intact and is not damaged. For this reason, the procedure can be repeated safely and is also suited to regions where laser treatments and deep peels cannot be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
212
1
21

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(250 citation statements)
references
References 35 publications
16
212
1
21
Order By: Relevance
“…10 In our study, we observed that many patients in group "A" reported improvement in the firmness of the face giving a lifted appearance which was intact for months even after the completion of the study. This effect was also reported in other studies such as that by Imran et al and Aust et al The firmness was probably due to continuation of deposition of collagen and elastin upto 6 months after the procedure which was confirmed histologically in the study done by Aust et al 11 This lifted appearance provided extra anti-aging effects in our patients. Microneedling can provide both acne scar remodelling and anti-aging benefits in same sitting.…”
Section: Discussionsupporting
confidence: 77%
“…10 In our study, we observed that many patients in group "A" reported improvement in the firmness of the face giving a lifted appearance which was intact for months even after the completion of the study. This effect was also reported in other studies such as that by Imran et al and Aust et al The firmness was probably due to continuation of deposition of collagen and elastin upto 6 months after the procedure which was confirmed histologically in the study done by Aust et al 11 This lifted appearance provided extra anti-aging effects in our patients. Microneedling can provide both acne scar remodelling and anti-aging benefits in same sitting.…”
Section: Discussionsupporting
confidence: 77%
“…In microneedling with dermaroller, there are fine needles which puncture the skin and cause increased elastin and collagen content in the dermis, collagen remodeling and increase in thickness of epidermis and dermis. 15 In subcision a small needle is inserted beneath the scar to loosen the fibrotic adhesions. Along with loosening of tissue there is also some bleeding at the site which creates a potential space where collagen can be deposited during the wound healing phase CO 2 lasers have a selectivity for water and it has a double effect that is, they promote the wound healing process and arouse an amplified production of myo-fibroblasts and matrix proteins such as hyaluronic acid.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, new capillaries are formedthis neovascularisation and neocollagenesis following treatment leads to reduction of scars. [3][4][5] The procedure was therefore aptly called "percutaneous collagen induction therapy" and has also been used in the treatment of photoageing.…”
Section: Discussionmentioning
confidence: 99%